The Alpha-Tocopherol Form of Vitamin E Boosts Elastase Activity of Human PMNs and Their Ability to Kill Streptococcus pneumoniae - Bou Ghanem, Elsa N.; Lee, James N.; Joma, Basma H.; Meydani, Simin N.; Leong, John M.; Panda, Alexander (Frontiers in Cellular and Infection Microbiology, 2017)
Despite the availability of vaccines, Streptococcus pneumoniae remains a leading cause of life-threatening infections such as pneumonia, bacteremia and meningitis. Polymorphonuclear leukocytes (PMNs) are a key determinant of disease course, because optimal host defense requires an initial robust pulmonary PMN response to control bacterial numbers followed by modulation of this response later in infection. The elderly, who manifest a general decline in immune function and higher basal levels of inflammation, are at increased risk of developing pneumococcal pneumonia. Using an aged mouse infection model, we previously showed that oral supplementation with the alpha-tocopherol form of vitamin E (α-Toc) decreases pulmonary inflammation, in part by modulating neutrophil migration across lung epithelium into alveolar spaces, and reverses the age-associated decline in resistance to pneumococcal pneumonia. The objective of this study was to test the effect of α-Toc on the ability of neutrophils isolated from young (22-35 years) or elderly (65-69 years) individuals to migrate across epithelial cell monolayers in response to S. pneumoniae and to kill complement-opsonized pneumococci. We found that basal levels of pneumococcal-induced transepithelial migration by PMNs from young or elderly donors were indistinguishable, suggesting that the age-associated exacerbation of pulmonary inflammation is not due to intrinsic properties of PMNs of elderly individuals but rather may reflect the inflammatory milieu of the aged lung. Consistent with its anti-inflammatory activity, α-Toc treatment diminished PMN migration regardless of donor age. Unexpectedly, unlike previous studies showing poor killing of antibody-opsonized bacteria, we found that PMNs of elderly donors were more efficient at killing complement-opsonized bacteria ex vivo than their younger counterparts. We also found that the heightened antimicrobial activity in PMNs from older donors correlated with increased activity of neutrophil elastase, a serine protease that is required to kill pneumococci. Notably, incubation with α-Toc increased PMN elastase activity from young donors and boosted their ability to kill complement-opsonized pneumococci. These findings demonstrate that α-Toc is a potent modulator of PMN responses and is a potential nutritional intervention to combat pneumococcal infection.